Performance Analysis of College Student Leadership Skills During Covid-19 Through Online Extra-Curricular Activities - Ermeey Abd Kadir; Mohd Nazrul Sidek, (Journal of Human Development and Communication (JoHDeC), 2025)
Covid-19 has hit our way of life in every aspect. Our education system is also included. Before the pandemic starts, most higher learning institutions use a face-to-face approach, and extra-curricular activities also follow the same way. New normal is a popular term nowadays. Every college student activity is required to adapt and tune to meet their objective. Student affairs units are required to investigate the new term and adjust accordingly. The unit is responsible for the development of the student's soft skills. This research reported the finding on how the unit adapts to the procedure of organising student activities. An online platform has its advantages and disadvantages. Still, in this research, the student feedback who organises an event during two different situations are recorded to get first-hand data on whether student skills like Leadership, Communication and Teamwork are well developed, especially during the pandemic. Data from student feedback reported that students had organised more than 150 activities through their society. The popular program is on academics, sports and recreation and volunteerism. During the pandemic, spiritual event shows an increase. Furthermore, these types of programs are the attributes of preparing a student to be excellent in leadership.